Formulation and Evaluation of Celecoxib and Apixaban Emulgel for Topical Delivery - Sahoo, Amaresh Chandra; Dash, Sujit; Sahoo, Prabhat Kumar; Sahoo, Minaketan (International Journal of Pharmaceutical Investigation, 2025)
Background Emulgel is a combination of gel and emulsion. Drugs are first incorporated into an emulsion and then the conventional emulsion is transferred into an emulgel by using a gelling agent. Objectives To formulate a stable o/w emulgel of an anti-inflammatory hydrophobic drug i.e., Celecoxib and anti-coagulant drug i.e., apixaban for enhanced permeability of drugs. Methods-Emulgel consists of both aqueous and oil phase. The aqueous phase consists of apixaban, tween 20 and oil phase composed of celecoxib, span 20 and liquid paraffin. Emulsion was prepared by mixing both the phases at 60ºC-70ºC, then this emulsion was incorporated into a gel using various types of gelling agent (Sod.CMC, Carbopol) having concentration of 2%, 3% and 4%. Light liquid paraffin was used as the oil, span 20, Tween 20 as emulsifier and propylene glycol as co-surfactant. The emulgel was evaluated for its various physicochemical parameters and in vitro release study of the formulated formulations were evaluated. Results and Discussion The pH, swelling index, viscosity, drug content of emulgel was found in the range of 5.8 to 6.4, 1.12 to 1.28, 1466 to 1742 cps, 91.06% to 96.31%. respectively. The cumulative percent drug release of the apixaban and celecoxib from Carbopol emulgel is 98%, 92%, 81% and 94%, 89%, 75% respectively whereas the cumulative percent drug release of the apixaban and celecoxib from Sod.CMC emulgel is 93%, 88%, 79% and 91%, 84%, 75% respectively. The drug release profile is based on the zero-order plot and the Korsmeyer Peppas model. Conclusion All the prepared emulgel showed acceptable physical properties. Batch C2 is considered an optimal formulation because it achieved the maximum cumulative release of drugs and the ideal viscosity.
Keywords: Emulgel; Celecoxib; Apixaban; Simultaneous Estimation; Ex vivo